1995
DOI: 10.1136/oem.52.10.686
|View full text |Cite
|
Sign up to set email alerts
|

Reports of work related musculoskeletal injury among home care service workers compared with nursery school workers and the general population of employed women in Sweden.

Abstract: OBJECTIVES--To describe the nationwide occurrence of work related musculoskeletal injuries among all home care service workers in Sweden, and to identify relative risks and risk factors of the injuries. METHODS--The study was based on work related injuries reported to the Swedish occupational injury information system in 1990-1. The work related musculoskeletal injuries were divided into overexertion accidents and musculoskeletal diseases. The incidence of the injuries in female home care service workers was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 13 publications
3
50
1
2
Order By: Relevance
“…Briefly, beginning in the 1990s, population-based studies from Scandinavia [10][11][12][13] have documented PAS-related occupational injury and disability. In the United States, the rate of MSDs among PAS workers exceeded that among construction, mining and manufacturing workers [14] .…”
Section: Issn 2324-7940 E-issn 2324-7959mentioning
confidence: 99%
“…Briefly, beginning in the 1990s, population-based studies from Scandinavia [10][11][12][13] have documented PAS-related occupational injury and disability. In the United States, the rate of MSDs among PAS workers exceeded that among construction, mining and manufacturing workers [14] .…”
Section: Issn 2324-7940 E-issn 2324-7959mentioning
confidence: 99%
“…reported occupational injuries and reported work-related diseases and symptoms, are common among home care workers (HCWs), compared to other female human service occupations (Ono, Lagerströ m, Hagberg, Lindén & Malker, 1995). Musculoskeletal disorders are the most common registered occupational disorder among nursing personnel and HCWs (Ono et al, 1995;Meyer & Muntaner, 1999).…”
Section: Occupational Disorders Among Home Care Workersmentioning
confidence: 99%
“…reported occupational injuries and reported work-related diseases and symptoms, are common among home care workers (HCWs), compared to other female human service occupations (Ono, Lagerströ m, Hagberg, Lindén & Malker, 1995). Musculoskeletal disorders are the most common registered occupational disorder among nursing personnel and HCWs (Ono et al, 1995;Meyer & Muntaner, 1999). Various organizational conditions in work, especially related to emotional and physical demands, contributes to work-related disorders and work injuries among HCWs (Johansson, 1995;Aronsson, Astvik & Thulin, 1998;Brulin et al, 1998;Engkvist, Hjelm, Hagberg, Menckel & Ekenvall, 2000;Dellve, Lagerströ m & Hagberg, 2003).…”
Section: Occupational Disorders Among Home Care Workersmentioning
confidence: 99%
“…Similarly, Kim and colleagues found a modest increase in risk (OR=1.14; CI=1.08-1.19) for physical demands among PAS providers (Kim et al, 2010). Other studies of care providers have also found challenges in identifying the role of physical risk factors in WRMSDs or related disability (Ando et al, 2000;Simon et al, 2008), or determining the most problematic physical risk factor in home care (Cheung et al, 2006;Ono et al, 1995). Most of these studies, like ours, were self report surveys, and lacked validation from medical or disability records, which may lead to misclassification of cases or imprecision of the models.…”
Section: Temporal Factorsmentioning
confidence: 97%
“…With upwards of 44% of low back pain patients in the general working population reporting a recurrence within one year (Woolf & Pfleger, 2003), multiple episodes or chronicity among home care providers also needs to be considered. Although several studies have documented rates among home health nurses and aides, only a few have focused on paid PAS workers in the home (Kim et al, 2010;Meyer & Muntaner, 1999;Ono et al, 1995).…”
Section: Introductionmentioning
confidence: 99%